30. CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS WITH RECURRENT RENAL FIBRILLATION (Vietnam Journal of Community Medicine, 2023)
Objectives: Study to evaluate the results of treatment of recurrent kidney stones by percutaneous lithotripsy Methods: Analytical cross-sectional description of 89 patients with recurrent nephrolithiasis treated with percutaneous endoscopic lithotripsy. Results: Clinical characteristics of patients: 97.8% of patients had symptoms of low back pain. Hematuria accounted for 17.3%; renal colic accounted for 6.7%. Paraclinical characteristics: complex kidney stones accounted for 30.3%, patients with pyelonephritis accounted for 23.6%. The group of stones with the size of 2-3cm accounted for the largest proportion with 52.8%; the number of patients with 3 or more stones accounted for the most with 56.2%; gravel surface area from 300mm2 and less than 200mm2 are equivalent; The degree of pyelonephritis grade I and grade II accounted for the most with 59.6%. Percutaneous lithotripsy results: 65.2% of patients only need 1 puncture into the renal pelvis. Patients using 1 tunnel during lithotripsy accounted for 88.8%. Patients with calyx puncture from the middle calyx position mainly accounted for 82.0%. The results recorded 5 cases of complications during surgery and 13 cases of complications during surgery. Conclusion: The subcostal puncture into the posterior inferior calyx group is chosen by most surgeons. The superior or middle calyx access is convenient to access subcutaneous lithotripsy.
Keywords: Recurrent kidney stones; lithotripsy; size.